The Development of "Kampung Sayang Bunda" Program in Supporting The Golden Period of Childern in Sukorame Public Health Center - Pratamaningtyas, Susanti; Titisari, Ira; Rahmawati, Rahajeng Siri Nur (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2021)
The pandemic period had a negative impact on several sectors, especially health sector where the examination of pregnant women becomes limited. Not only the time, but many of them feel afraid of contracting covid 19 when going to public health care. This causes the increased of risk for mothers and babies in the first 1000 days of life so that “Kampung Sayang Bunda” program was formed. The purpose of this program was to provide assistance to pregnant women by volunteer students. The knowledge of pregnant women was assessed and analyzed using the Wilcoxon test with a sig 2-tailed value of 0.002, of which 0.002 less than 0.005. this suggests that there was a significant association in the influence of assistance on maternal knowledge about how much important health in the first 1000 days of life